The Political Direction of Indonesian Economic Law as the Conception of Welfare State in the 1945 Constitution - Imaniyati, Neni Sri; Yusdiansyah, Efik; Muhardi; Syam, Husni; Cheumar, Mohammad Tahir; Adam, Panji (International Journal of Criminology and Sociology, 2021)
Political law, political economy and political economy law are three concepts that arise from a deep understanding of the 1945 Constitution as statutory norms. A series that tries to align the interests and desires of the 1945 Constitution with the interests of the state and the people’s wishes, which often have different views and practices between the two. This article aims to analyze the direction of Indonesian economic law politics policy in the Welfare State conception based on the 1945 Constitution. The method used is a normative juridical approach with descriptive-analytical techniques using qualitative juridical data analysis methods. This article concludes that the direction of Indonesian economic policy shows some adoption of neoliberalism values that have become references in the formulation of monetary policy in Indonesia. As a government law politics, the direction of economic policy must be oriented towards the institutionalization of the status of the Indonesian nation to advance the general welfare. And the "vehicle" for institutionalizing this staatsidee, as formulated in Article 33 of the 1945 Constitution of the Republic of Indonesia, is the concept of a welfare state.